THE INFLUENCE OF WORD OF MOUTH AND BRAND IMAGE AGAINST PRODUCT PURCHASING DECISIONS APPLES - Sari, Hanny Putri Permata; Febriyantoro, Mohammad Trio (PT. Batari Edu Calya, 2023)
This study aims to determine the effect of word of mouth and brand image on purchasing decisions for Apple products. This research was conducted on users of Apple brand products. The population in this study are people who use Apple brand products. The technique used in this writing test uses a purposive sampling technique, namely a sampling technique with certain considerations. Data collection was carried out by providing a list of questions to respondents and tested using the SPSS data analysis method. Based on statistical tests, the results showed that word of mouth had a direct positive and significant effect on purchasing decisions, while brand image had a direct positive and significant effect on purchasing decisions. There is a significant influence between Word Of Mouth on purchasing decisions. And there is a significant influence between Brand Image on purchasing decisions.